A hybrid performance evaluation approach for urban logistics using extended cross-efficiency with prospect theory and OWA operator. Issue 1 (31st December 2023) - Jiang, Wenjun; Liu, Shuli; Wang, Weizhong
Abstract: Urban logistics performance evaluation can provide reference for further improving its level. However, most performance evaluation for urban logistics premises that decision-makers (DMs) are completely rational, which may not conform to the actual situation. Therefore, this article aims to consider the DMs' psychological factors in the performance evaluation of urban logistics. Specifically, the cross-efficiency evaluation (CEE) method with the DMs' psychological factors is used to measure the urban logistics efficiency in the central area of Yangtze River Delta (YRD) urban agglomeration in China in 2019. The main contributions in this article are to propose a hybrid CEE method with prospect theory and ordered weighted average (OWA) operator for urban logistics industry and to expand the evaluation perspectives of urban logistics performance. The main conclusions are obtained: (1) The DMs' optimism level can indeed affect the efficiency value and ranking of urban logistics. (2) The aggregation based on the OWA operator is fair and reasonable because it can make all self-evaluation efficiencies play the same role. (3) To make the efficiencies and rankings of urban logistics in the central area of the YRD have credibility and discrimination, the DMs' optimism level range is best between 0.8 and 0.8177.